The role of community radio in contributing to the entrepreneurial education of an Eastern Cape youth audience - Ngcobo, Nkosisphile (Rhodes University, 2026)
This study explores how community radio can be utilised to deliver entrepreneurial education to a South African youth audience. It focuses on Rhodes Music Radio (RMR) as a case study. RMR is a campus-based community radio station located on the Rhodes University campus in Makhanda. The study responds to South Africa’s ongoing youth unemployment crisis by investigating whether radio and community radio, in particular, can be leveraged to deliver knowledge and practical understanding about entrepreneurship. This is to empower young people, particularly those from marginalised and underprivileged backgrounds, to start and successfully run their own businesses. The study is practice-based and comprises a written thesis and a media production project in the form of a radio show, titled The BizTalk Show, broadcast on RMR. The show was first conceptualised and piloted, guided by insights drawn from literature about entrepreneurial education and community radio. Qualitative methods were then employed to assess the role that the show is able to play in contributing to entrepreneurial education. The focus is on the value of its location within a participatory mode of production. The assessment of the show draws on interviews with key stakeholder groups, which include the station management at RMR; the young people who volunteered to be part of the production team; the studio guests; and the youth who make up the audience of the show. The interviews were analysed, guided by insights drawn from the literature on entrepreneurial education and community radio. Findings suggest that youth-based community radio holds significant potential as a vehicle for entrepreneurial education because it prioritises participatory production practices that include the contributions of its audience. Such radio allows for the co-production of knowledge amongst all stakeholders, thus acknowledging the lived realities of youth as well as insights drawn from expert spheres of knowledge. However, the study also identifies challenges and limitations in the operation of The Biztalk Show, particularly with regard to the degree to which young people from outside the campus had been included in participation in the show. It is argued that this limitation must be addressed not only in the context of the show but more broadly within RMR. It is also noted, however, that young people on campus are legitimate beneficiaries of the show, given that they come from marginalised backgrounds and continue to face challenges with regard to future employment. The research contributes to broader discussions on media for development, education outside formal institutions, and the urgent need to address youth unemployment in South Africa.
a case study of The BizTalk Show on Rhodes Music Radio
Keywords: Uncatalogued